(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
Art and measure were the privileged places in which Lucio Saffaro’s meditations (Trieste 1929 – Bologna 1998) started. A constant and peculiar combination that led him to such a rigorous work, between the internal structures of science and art, that it allowed him to overcome the distinction problem between the two disciplinary dichotomies. Rightly, the consistency of his investigative process, where the artist, while using classical instruments and languages, was able to contradict them from the inside, creating new, entirely original optical theories and alphabets, was visible. Saffaro considered science with the poet’s eye and faced art with the tools of the ma- thematician, without, however, being entangled in the didactic chains of purely interdisciplinary proceedings. In fact, the seriousness of his inquiry led him to a heuristic territory where writing, painting and scientific thought were formulated by a single reflection, structured not by disagre- ements but by coherent and recurring parallelisms.